Skill progression pathways and head kinematics in men`s artistic gymnastics - Romero A., G. A.; Pritchard, N. S.; Brandt, K. M.; Bullock, G. S.; Peluso, A. G.; Kruse, D. W.; Miles, C. M.; Moore, J. B.; Agee, J. M.; Young, C.; Stitzel, J. D.; Urban, J. E. (Journal of Sports Sciences, 2025)
This study aimed to evaluate head kinematics during skills performed within common skill progression pathways in men`s artistic gymnastics. Eight men`s artistic gymnasts (ages 11-18) wore mouthpieces with triaxial accelerometers and gyroscopes and performed skills from seven skill progression pathways: backward and forward tumbling on the floor, bar/ring elements, releases, dismounts, Tsukahara vaults, and Yurchenko vaults. Data were recorded at 100 Hz for 10-min periods and were time-synchronized with video footage. Peak linear acceleration (PLA), peak rotational acceleration (PRA), resultant change in rotational velocity during the maximum rotational acceleration (?RV), and peak rotational velocity (PRV) were compared across skills within each skill progression pathway using mixed effects models, accounting for participant variability. Head kinematics were not always aligned with gradual advancements in skill complexity through a skill progression pathway. For example, preparatory skills where the gymnast`s head engages a surface (e.g. timers) can expose gymnasts to high magnitude head kinematics. Additionally, back handsprings and somersaults with twists exposed gymnasts to the greatest PRV. Post-concussion return-to-sport protocols should account for the diverse biomechanical demands imposed by each skill, facilitating sport-specific and biomechanically informed progressions back into sport post-injury.